ANALISIS SITOGENETIKA PADA TANAMAN KAILAN (Brassica oleraceae L.) - Syahputra, Akbar; Febriani, Husnarika; Idami, Zahratul (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2024)
Cytogenetics is a combination of cytology and genetics which studies the genetic system in cells. Cytogenetic analysis is a combination of cytogenetics (about cells) and genetics which explains the relationship between cellular events (especially chromosomes) and genetic phenomena. The objects observed in cytogenetic analysis are chromosomes. Cytogenetic analysis research has been carried out on kailan plants (Brassica oleraceae L.) with the aim of observing the effective time of mitotic division in kailan plants, the stages of mitotic division, the number and shape of chromosomes in kailan plants (Brassica oleraceae L.). The material used in this research is young roots of the kailan plant. The method used in this research is the squash method. The results of cytogenetic analysis research on kailan plants (Brassica oleraceae L.) showed that the effective time of mitotic division was 08.00 WIB and obtained an overview of the stages of prophase, prometaphase, metaphase, anaphase and telophase, the number of chromosomes of kailan plants (Brassica oleraceae L.) was 2n = 9 pairs of chromosomes or 18 chromosomes, with 5 pairs of metacentric chromosome forms in numbers 2, 3, 4, 5, and 8, and 4 pairs of submetacentric forms in numbers 1, 6, 7, 9.